(untitled) (Journal of Vishwa Adarsha College, 2025)
The technological and scientific progress, including the COVID-19 pandemic, has expedited the transition to online teacher professional development. Webinars have emerged as a common platform for language educators to acquire and enhance their professional skills for growth. This autoethnographic study reveals the experiences of an English language teacher participating in national and international webinars during and after the pandemic. It examines the value and benefits of attending webinars as a means of professional development for educators. The primary source of data collection is the researchers’ own life experiences in attending the webinars, which have lasted from 30 minutes to two-hour-long sessions via virtual modes. The possible areas of discussion in the webinar include teachers’ professional practices, classroom management, teacher motivation, pedagogical tips, and ICT-related skills. It explores the anecdotes, reflections, memories, screenshots, and experiences of participation in various national and international webinars through the lens of Kolb’s Experiential Learning Theory. The findings show that webinars play a significant role in online teacher professional development by expanding knowledge and competencies, fostering networking, becoming effective teaching tools, and applying newly acquired competencies to classroom practice. The study also shows some challenges encountered in attending webinars. The first author, employing the first-person pronoun "I," composed this paper on the basis of his online teacher professional development experiences. The second author wrote, reviewed, edited the article, and gave suggestions to the first author accordingly based on similar practical conditions and experiences. As an autoethnography approach, we decided to tell this story through “I” to properly illustrate the details that have been foregrounded with the first author’s experiences.